#Polar Scores: Measuring partisanship using social media content. Issue 4 (1st October 2016) - Hemphill, Libby; Culotta, Aron; Heston, Matthew
ABSTRACT: We present a new approach to measuring political polarization, including a novel algorithm and open source Python code, which leverages Twitter content to produce measures of polarization for both users and hashtags. #Polar scores provide advantages over existing measures because they (a) can be calculated throughout the legislative cycle, (b) allow for easy differentiation between users with similar scores, (c) are chamber-agnostic, and (d) are a generic approach that can be applied beyond the U.S. Congress. #Polar scores leverage available information such as party labels, word frequency, and hashtags to create an accessible, straightforward algorithm for estimating polarity using text.